Translation and validation study of the Indonesian version of the practice environment scale of the nursing work index - I Gede Juanamasta; Yupin Aungsuroch; Mary L. Fisher; Siluh Nyoman Alit Nuryani; Ni Nyoman Ayuningsih (Elsevier, 2023)
Objectives: This study aimed to translate and validate the Practice Environment Scale - Nursing Work Index (PES-NWI) among nurses in Indonesia. Methods: A scale translation and cross-sectional validation study was conducted. The English version was translated into Indonesian, which involved five steps: forward translation, compare the translation, backward translation, compare the translation, and pilot testing with a dichotomous scale (clear or unclear). Thirty inpatient department nurses were involved in checking readability and understandability. A cross-sectional study was conducted from August to October 2022 at 17 hospitals across Indonesia, involving 350 nursing professionals. The validity test included structural validity and convergent validity. The internal consistency reliability was tested by Cronbach's α coefficient, item-total correlation, and composite reliability. Results: Confirmatory factor analysis (CFA) showed an acceptable fit. The correlation of all dimensions was between 0.70 and 0.88, and all items had item loading higher than 0.6. Convergent validity of each dimension ranged from 0.61 to 0.74, internal consistencies with Cronbach's α coefficient was 0.97, corrected item-to-total correlation ranged from 0.62 to 0.85, and composite reliability of each dimension was higher than 0.89. Conclusions: Good homogeneity and construct validity have been demonstrated for the Indonesian version of the PES-NWI, nursing management can use it to measure the work environment.